Collected Papers VI. Literary Reality and Relationships - Schutz, Alfred. author. aut Link
VI, 414 p.
Keywords: The three essays in this volume illuminate Alfred Schutz’s understanding of literature and literary relationships. The first, “Life Forms and Meaning Structures,” presents such ideal life-forms as duration, memory, the speaking ego, and the I in relation to the Thou. This essay also describes the fundamental nature of human experience, its pluralized realms, the passage of time, perspectival interpretation, action and its impediments—all concepts which make possible an understanding of literature and literary themes. The essay goes on to discuss opera, and the relationship between music and language in opera. The second essay, “The Problem of Personality in the Social World,” offers insights into the unity the social person achieves, temporality, and the role of the body and the importance of pragmatic relevances. This shows how, even before he arrived in the United States, Schutz went beyond his 1932 Phenomenology of the Social World in a pragmatic direction. This essay anticipates Schutz’s 1945 essay, “On Multiple Realities,” by discussing reality-spheres of working, phantasy, dreams, and theory. Reality-spheres are vital for understanding literature, as shown in the third essay, which translates for the first time two Goethe manuscripts produced by Schutz in 1948. The first text, on Lehrjahre, reveals Schutz actually interpreting a piece of literature, tracing the themes of art and life and fate and freedom through the text. The second, a commentary on Goethe’s Wanderjahre, presents an inchoate theory of literature. Defending Goethe’s 1829 version of the Wanderjahre novel, Schutz argues that critics miss the point that readers of literature adopt a specific kind of epoché in which they enter a reality-sphere governed by “the logic of the poetic event,” whose rules are notthose of everyday life or theoretical contemplation. In sum, this volume brings out the distinctive character of literary reality and the relationships between author and reader, and invites the reader to derive a sense of how Schutz himself read literature. .